Mid-Infrared Detectors for Space Electronics Based on InAs-core/InP-Shell Nanowires - Vinnichenko, M. Ya.; Ustimenko, R. V.; Karaulov, D. A.; Firsov, D. A.; Fedorov, V. V.; Mozharov, A. M.; Kirilenko, D. A.; Mukhin, I. S.; Sarkisyan, H. A.; Hayrapetyan, D. B.; Kazaryan, E. M.
The Mid-Infrared (MIR) spectral range is most important for free-space communications and astronomy. It contains radiation emitted by astrophysical objects during evolution of the planets, stars, galaxies and in particular by prebiosignature molecules on exoplanets. Nanowires (NWs) are expected to improve various optoelectronic devices, including IR photodetector technology. The bandgap of the catalystless InAs NWs can be tuned by introducing mechanical strain due to lattice mismatches in the core/shell NWs structures. Passivation with wider bandgap InP shell provide highly tunable functionality for future electronic devices. Temperature dependence of photoluminescence (PL) spectra of NWs InAs and InAs-core/InP-shell was acquired using Fourier-spectrometer. The position of the high-energy PL peak between calculated values of Eg for wurtzite and sphalerite structures confirms the formation of NWs into a combined polytype. Low energy PL peak is connected with parasitic bulk islands. Surface passivation successfully eliminates surface states and provides nontrivial temperature dependence of high-energy PL peak due to tensile and compressive strain in InAs core. Thus, detectors based on NWs InAs and InAscore/ InP-shell structures can operate in the MIR range of the spectrum with a wavelength from 2 to 5 μm
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture